2021
DOI: 10.1017/s0033291721002129
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sensorimotor-to-transmodal hierarchical organization in schizophrenia

Abstract: Background Schizophrenia has been primarily conceptualized as a disorder of high-order cognitive functions with deficits in executive brain regions. Yet due to the increasing reports of early sensory processing deficit, recent models focus more on the developmental effects of impaired sensory process on high-order functions. The present study examined whether this pathological interaction relates to an overarching system-level imbalance, specifically a disruption in macroscale hierarchy affecting integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 91 publications
(163 reference statements)
4
56
0
Order By: Relevance
“…In the present study, we found that individuals with higher behavioral (general psychopathology) composites in LV1 have diminished differentiation between the sensorimotor and supramodal cognitive systems within cerebellar functional principal gradient organizations across psychiatric diagnoses, which is conceptually consistent with our previous studies ( Dong et al, 2020 , Dong et al, 2021 ) and other researcher ( Elliott et al, 2018 ). In our previous studies, we found schizophrenia patients showed diminished differentiation in intra-cerebellar, cerebellar-cerebral gradient and cerebral-cerebral gradient.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that individuals with higher behavioral (general psychopathology) composites in LV1 have diminished differentiation between the sensorimotor and supramodal cognitive systems within cerebellar functional principal gradient organizations across psychiatric diagnoses, which is conceptually consistent with our previous studies ( Dong et al, 2020 , Dong et al, 2021 ) and other researcher ( Elliott et al, 2018 ). In our previous studies, we found schizophrenia patients showed diminished differentiation in intra-cerebellar, cerebellar-cerebral gradient and cerebral-cerebral gradient.…”
Section: Discussionsupporting
confidence: 93%
“…2000 instead of 4,000,000 datapoints (see Figure 8 and [16] for an example). Other examples of studies using functional gradients to detect differences in patient populations in structures other than the cerebellum include [17][18][19].…”
Section: Practical Application Vii: Identification Of Functional Abno...mentioning
confidence: 99%
“…Limitations specific to functional gradients analyses are mostly related to the novelty of this field, and include the lack of standardization for the calculation of functional gradients, the absence of a solidified framework for the interpretation of functional gradient abnormalities in patient populations, and the paucity of experiments analyzing functional gradient anatomy at the singlesubject level. Efforts to address these issues are ongoing, including the development of toolboxes for the generation of functional gradients [11,31], the emergence of a field of functional gradient research that is focused on patient populations [16][17][18][19], and preliminary data supporting that general principles of functional gradient organization in the average cerebellum remain observable in individual subjects [1,16].…”
Section: Limitationsmentioning
confidence: 99%
“…Reconstruction of macroscale brain connectome in first-episode schizophrenia patients by combining DWI and fMRI data revealed that connectome rich club structures exhibited significant impairment in medication-naïve patients, which provides further evidence that brain connectivity disruption may play an important role in the early stage of schizophrenia pathophysiology [15]. A recent fMRI study combining connectome gradient and stepwise connectivity analysis demonstrated abnormal compression of sensorimotor-to-transmoda cortical hierarchy organization in schizophrenia, providing new insight into the pathological relationship between early sensory and cognitive impairment [16].…”
Section: Providing Evidence Of Macro-scale Neural Mechanismsmentioning
confidence: 83%